Molecular basis of the urate transporter URAT1 inhibition by gout drugs - Yang Suo; Justin G. Fedor; Han Zhang; Kalina Tsolova; Xiaoyu Shi; Kedar Sharma; Shweta Kumari; Mario Borgnia; Peng Zhan; Wonpil Im; Seok-Yong Lee (Nature Communications)
Abstract Hyperuricemia is a condition when uric acid, a waste product of purine metabolism, accumulates in the blood. Untreated hyperuricemia can lead to crystal formation of monosodium urate in the joints, causing a painful inflammatory disease known as gout. These conditions are associated with many other diseases and affect a significant and increasing proportion of the population. The human urate transporter 1 (URAT1) is responsible for the reabsorption of ~90% of uric acid in the kidneys back into the blood, making it a primary target for treating hyperuricemia and gout. Despite decades of research and development, clinically available URAT1 inhibitors have limitations because the molecular basis of URAT1 inhibition by gout drugs remains unknown. Here we present cryo-electron microscopy structures of URAT1 alone and in complex with three clinically relevant inhibitors: benzbromarone, lesinurad, and the recently developed compound TD-3. Together with functional experiments and molecular dynamics simulations, we reveal that these inhibitors bind selectively to URAT1 in inward-open states. Furthermore, we discover differences in the inhibitor-dependent URAT1 conformations as well as interaction networks, which contribute to drug specificity. Our findings illuminate a general theme for URAT1 inhibition, paving the way for the design of next-generation URAT1 inhibitors in the treatment of gout and hyperuricemia.